Enfoques de aprendizaje en estudiante de quinto nivel de educación inicial en la facultad de ciencias de la educación y humanidades de la Universidad Nacional de la Amazonía Peruana, Iquitos 2021 - Vasquez Flores, Rosario de Fatima (2023)
The present research was carried out with the purpose of describing the level of application of learning approaches in students of the fifth level of initial education of the Faculty of Educational Sciences and Humanities at the National University of the Peruvian Amazon, located in Iquitos in the year 2021. The methodology used the type of descriptive research, associated with a cross-sectional, field, cross-sectional and univariate design. The population and sample consisted of 33 students from the fifth level of initial education. The data collection technique was the survey, and a questionnaire was applied as an instrument, which was previously validated by expert judgment. The conclusion of the research is that the level of application of learning approaches in students of the fifth level of initial education of the Faculty of Educational Sciences of the National University of the Peruvian Amazon is good at 60.6%, very good at 36.4% and regular for 3.0% of the students.